Análise estabilométrica em indivíduos submetidos à tarefa de realidade virtual: Um estudo cross-over - Almeida, Maxwell (2020)
Introduction: In the last decade, virtual (VR) has gained ground as a treatment tool for several sequelae from different areas of Physiotherapy. An RV can be defined as a projection of those suitable for a virtual scenario where they can interact, through their senses, using body movements promoting an interrelation with the scenario. However, there is still a shortage in the literature on the use of this resource for balance deficit, which was a motivational factor in carrying out this work. Objective: To analyze possible acute changes in forced developments to VR, comparing the possible changes in the stabiliometric parameters in the research participants in two experimental conditions: real vs. virtual reality. Methodology: In this cross-over experimental study, 45 healthy participants were analyzed submitted to two experimental conditions: real task (TR) and virtual reality task (TRV). Initially, the participants answered an identification questionnaire (Appendix) and later performed the task of walking on a board (TR) and, soon after, the same task in the TRV with the game Richie’s Plank Experience. For the analysis of static balance, the force platform (AccuSwayPlus) was used. The stabilometric variables analyzed were: the elliptical area, the speed and the acceleration to detect possible changes between the experimental conditions open base (BA) and closed base (BF). For the sample calculation, ANOVA 2x2 was used for repeated measures. Statistical analysis: A two-factor ANOVA was used to identify the main effects and interaction between the support base and the moment. Results: As a result, we observed that there was a main effect of the support base for the variable DPml (F=61,339, P<0,011, 2=0,363), reflecting the increase in the mediolateral displacement of the CP in the closed base. For the DPap variable, there was a main effect at the moment (F=4,427, P=0,041, 2=0,037), observing an increase in the anterior-posterior displacement of the CP in the post-RV moment, compared to the pre-VR moment. An increase in the values of CP velocities was observed both in the post-RV and in the closed base, when compared with those obtained in the open base and in the pre-RV moment, respectively. Conclusion: With the results obtained in this research, it can be concluded that VR compared to RT, promotes immediate changes in the static balance, showing that this type of intervention is able to promote a stimulus to the participant's stability. Our findings point to indications that VR may be a tool to be used to treat balance deficits.